2013
DOI: 10.1590/s1982-56762013005000012
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização fisiológica de isolados de Corynespora cassiicola

Abstract: RESUMOCorynespora cassiicola, agente causal da mancha alvo, causa prejuízos econômicos em diversas culturas. Como a disponibilidade de protocolos padronizados para a produção de inóculo facilitam a condução de testes de patogenicidade, os objetivos deste trabalho foram analisar o crescimento micelial em diferentes temperaturas; avaliar o crescimento micelial e a esporulação de isolados obtidos de diferentes hospedeiros em diferentes regimes de luz; avaliar o efeito da duração de umidade contínua para a máxima … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 13 publications
1
13
0
6
Order By: Relevance
“…Our results did not agree with the observed by Teramoto et al, (2013a) that reported significant interaction for six Brazilian C. cassiicola isolates and twelve soybean cultivars in a single assessment of disease severity. The high variability reported for the fungus aggressiveness Teramoto et al, 2013b) and in the host resistance did not implied an interaction effect for the present experimental conditions.…”
Section: Discussionsupporting
confidence: 40%
“…Our results did not agree with the observed by Teramoto et al, (2013a) that reported significant interaction for six Brazilian C. cassiicola isolates and twelve soybean cultivars in a single assessment of disease severity. The high variability reported for the fungus aggressiveness Teramoto et al, 2013b) and in the host resistance did not implied an interaction effect for the present experimental conditions.…”
Section: Discussionsupporting
confidence: 40%
“…It is known that the abuse of systemic molecules to control pathogens causes reduction in the sensitivity to products (Reis et al, 2010). In some studies, the fungicide carbendazim had low efficiency in controlling the target spot, which could have been as a result of the resistance to this chemical group on the pathogen (Teramoto et al, 2013;Avozani et al, 2014). However, in this work, carbendazim fungicide did not appear to be inefficient in its toxicity.…”
Section: Cassicola Isolatesmentioning
confidence: 56%
“…En los ciclos productivos de 2014 y 2015 para Ayutla y Tecoanapa, las temperaturas promedio oscilaron entre 25.01 °C y 28.24 °C con humedades relativas entre 71.46% y 95.67% (Tabla 3). En base a lo reportado por Teramoto et al (17), mencionan que las temperaturas entre 23.3 °C a 29.5 °C y alta humedad relativa (100%) (2) son favorables para C. cassiicola, condiciones similares fueron registradas en el presente estudio (Tabla 3).…”
Section: Resultados Y Discusiónunclassified